Intravenous Immunoglobulin Utilization in a Pediatric Tertiary Care Teaching Hospital in Iran: IVIG Utilization in a Pediatric Hospital - Kargar, Mona; Nikahd, Mohammad-Hadi; Amini, Shahideh; Heidari, Kazem; Gholami, Kheirollah (Iranian Journal of Pharmaceutical Sciences, 2019)
Intravenous immunoglobulin (IVIG) is an expensive medicine which is widely used for unlabeled indications. We conducted this drug utilization review (DUR) to evaluate the appropriateness of IVIG utilization in Tehran, Iran. This cross sectional study was conducted in a referral pediatric tertiary care hospital in Tehran. During a three month period in 2015, medical records of inpatients with IVIG order were evaluated. Appropriate indications for IVIG were determined based on the evidenced based guidelines and literature. Medical records of patients were reviewed and demographic data as well as the diagnosis, previous treatments, IVIG indication, dose, duration and the adverse drug reactions (ADR) were documented. Additionally, cost of therapy was calculated. During the study, 115 patients received IVIG. In 51 cases (44.4%), a total of 1338 gram IVIG was administered inappropriately. We found that in 32 cases (27.8%), intractable epilepsy was the inappropriate indication. The most frequent prescribers of IVIG were clinical specialists of pediatric neurology, pediatric asthma and immunology followed by pediatric hematology. In terms of safety, we found that 64 (55.6%) patients experienced at least one ADR. The most prevalent ADRs were hypotension (27.8%), fever (26.9%) and chills (18.3%). Total cost of IVIG during the study period was 6,075,500,000 Rials (approximately 215,872 ). Irrational use of IVIG is still a considerable issue that costs a considerable amount. Due to the high cost of therapy, multifaceted interventions are necessary to be implemented to improve the prescribing practice.